Geology of the Flin Flon Area:: A New Look at the Sunless City - Stauffer, Mel (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1974)
Summary Although economic development has initiated more geological work in the Flin Flon area than any other part of the Precambrian Shield in Saskatchewan, it is only recently that the detailed geological, geophysical, and geochemical work necessary to gain a firm understanding of the area has begun. The results of this work are far from conclusive at present. However, a tentative geotectonic setting can be interpreted for the development of the area. During Aphebian time, the Amisk Group of volcanic rocks were deposited as an island-arc complex. Continued closure of the Aphebian "Churchill Ocean" and concomitant subduction zone processes resulted in intrusion, uplift, and formation of the Missi Group of coarse clastic sediments as a molasse deposit. Finally, abutment of this complex with either older Aphebian arc complexes or the Archean Superior Province craton resulted in metamorphism, intrusion, and at least three phases of deformation during the Hudsonian orogeny.